Grazing systems and supplementation effects on tropical forage-based dairy systems in the dry season - Zanette, Isabela E. B.; Sousa, Daniel P.; Paula, Nelcino F. de; Santos, Alyce R. M.; Macedo, Bruna G.; Costa, Rayanne V. [UNESP]; Camargo, Karine D. V. [UNESP]; Carvalho, Perivaldo; Cabral, Carla H. A.; Cabral, Carlos E. A. (Elsevier B.V., 2020)
In dairy production systems, the use of strategies to increase production can be used, however some care must be taken to avoid the loss of nitrogen in the system, which is directly related to the environmental impacts. The aim with this study was to evaluate and the effect of the use of CP levels in concentrate in intensive systems on the productive performance and nitrogen metabolism of dairy cows in a tropical forage-based system. Sixteen multiparous Holstein-Zebu crossbreed cows in the middle and final third of lactation were used in a replicated 4 x 4 Latin square design with a 2 x 2 factorial arrangement of treatments design with 2 grazing systems (traditional and intensive) and 2 CP levels (18 and 22% CP) in concentrate. In intensive system, fertilization and irrigation were performed, while in traditional system, there was no fertilization and irrigation. Grazing systems affected all milk yield and composition variables, except for milk protein and solids. Greater milk yield was observed for cows in intensive system. Milk solids content was greater for cows supplemented with 18% CP level. Milk fat, protein, lactose, and solids yield was greater for cows in intensive system. Nitrogen use efficiency was greater for cows in traditional system. Milk N excreted was similar between supplemented cows, however, it was greater for cows in intensive system compared to cows in traditional system as well as 22% CP level. There was a grazing systems effect for ruminal ammonia nitrogen concentration with lesser values for cows in traditional system. The 22% CP level increased ruminal ammonia nitrogen. The results obtained in this study showed that cows in pastures under intensive system showed protein and energy imbalance in the rumen. The increase in CP levels does not affect the productive characteristics of these animals, only resulting in higher costs and higher N excretion to the environment.
Keywords: Dairy cattle; Irrigation; Nitrogen fertilization; Nitrogen metabolism; Protein supplementation